SINERGI ANTARA TRIPUSAT PENDIDIKAN ISLAM DI KECAMATAN NONGGUNONG KABUPATEN SUMENEP - Zainol Huda (Fakultas Tarbiyah, Universitas Ibrahimy, 2019)
The responsibility of Islamic education cannot be carried out unilaterally. Ki Hajar Dewantara stated that it requires the cooperation of three components which called as tripusat pendidikan education (center of three in education), they are families, educational institutions, and society. Those three components are one unit and complement each other. This is what happened at MTs Zainur Ridla (Islamic Junior High School Zainur Ridla) and MTs. Bustanul Ulum (Islamic Junior High School Bustanul Ulum), both of them are in Nonggunong District, Sumenep Regency. The findings in this research indicate that student’s guardians in MTs Zainur Ridla and MTs Bustanul Ulum Nonggunong have awareness about the responsibility of Islamic education. Second, all teacher councils in those two Islamic Junior High School stated that educating responsibility was on their control with habituation for their students in the form of reciting Shalawat Nariyah, reciting short surahs before the lesson began, praying before and after the lesson, shaking hands with teacher councils when coming and going home. Third, the participation of the society in realizing the responsibility of Islamic education through the media and the tradition of Kompolan. Fourth, the pattern of cooperation between madrasah (school) and student’s guardians in the form of: Home visits, inviting student’s guardians, forming madrasah supporting body, and report cards. While the pattern of cooperation between madrasah and society is their involvement in PHBI (Commemoration Islamic Feast Day) activities, their involvement in camp activities, their involvement in accepting new students, and their involvement in enforcing the discipline and regulations at madrasah.